Прощальное эхо: [роман] / Анна Смолякова - Смолякова Анна Владимировна (Баттерфляй, 1997)
Экземпляры: РБ (20230830) / Инвентарный номер: 66291 / Цена: 10.00 / Авт.знак: С 51 / ГРНТИ: 17.82 / ББК: 84(2Рос=Рус)6